Study on Stress Evolution and Crushing Behavior of Jointed Rock Mass under Confining Pressure and Joint Materials. (4th March 2023) - Qirui, Wang; Qihu, Zhang; Liyun, Yang; Fuli, Kong; Chenxi, Ding; Junqi, Fan
Abstract : To study the effects of confining pressure and joint material properties on stress evolution and fracture behavior of jointed rock mass under SHPB impact load, the numerical software LS-DYNA and the indoor SHPB impact system are used to carry out experimental research on intact rock mass and jointed rock mass. The peak stress, reflection and transmission coefficient, and specimen failure state of rock specimens under different schemes are obtained. The effects of confining pressure level and joint material properties on the propagation and attenuation law of explosive stress waves are expounded. The test results show that when the confining pressure is within a specific range, the impact resistance of the limestone specimen can be increased, and the more difficult it is to be destroyed. Moreover, if the confining pressure continues to increase after rising to the peak value, the impact resistance of rock specimens will decline. In that case, the impact resistance of the specimen will decrease—the dynamic strength of jointed rock mass changes with a change in joint material. The dynamic strength of cement jointed rock is the highest, that of gypsum jointed rock is the second, and that of epoxy resin jointed rock is the lowest. The impact damage resistance of the jointed rock has the same law as the above.